2003
DOI: 10.1002/jmri.10380
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of dynamic contrast enhancement MRI parameters with microvessel density and VEGF for assessment of angiogenesis in breast cancer

Abstract: Purpose:To investigate the association between parameters obtained from dynamic contrast enhanced MRI (DCE-MRI) of breast cancer using different analysis approaches, as well as their correlation with angiogenesis biomarkers (vascular endothelial growth factor and vessel density).Materials and Methods: DCE-MRI results were obtained from 105 patients with breast cancer (108 lesions). Three analysis methods were applied: 1) whole tumor analysis, 2) regional hot-spot analysis, and 3) intratumor pixel-by-pixel anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
116
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(122 citation statements)
references
References 40 publications
6
116
0
Order By: Relevance
“…Microvessel density does not reflect the functional properties of vessels, including permeability, which contribute to DCE-MRI variables. Studies reporting correlation between MRI variables and MVD have therefore found only moderate associations (Su et al, 2003;Tuncbilek et al, 2004). Several studies (Buckley et al, 1997;Stomper et al, 1997;Su et al, 2003) show conflicting data relating immunohistochemical expression with DCE-MRI data.…”
Section: Discussionmentioning
confidence: 99%
“…Microvessel density does not reflect the functional properties of vessels, including permeability, which contribute to DCE-MRI variables. Studies reporting correlation between MRI variables and MVD have therefore found only moderate associations (Su et al, 2003;Tuncbilek et al, 2004). Several studies (Buckley et al, 1997;Stomper et al, 1997;Su et al, 2003) show conflicting data relating immunohistochemical expression with DCE-MRI data.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Several morphologic characteristics and kinetic patterns on MR imaging in breast carcinoma are explained primarily by the histological structures and the degree of tumor angiogenesis. [9][10][11][12][13][14][15] In addition, tumor vascularity detected on imaging may be in‰uenced by the histological growth pattern of the carcinoma, such as scirrhous or solidtype carcinoma. 16 In our study, mass margin (Pº0.001) and kinetic pattern (P=0.04) were signiˆcantly diŠerent among the 3 SCD groups.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several morphologic characteristics and kinetic patterns on MR imaging in breast carcinoma are primarily explained by the histological structures of the lesions, [9][10][11] such as centralˆbrosis, central necrosis, marginalˆbrosis, and the degree of tumor angiogenesis. 9,10,[12][13][14][15] However, we previously reported that the tumor vascularity of breast carcinoma on power Doppler ultrasonography depended not only on the degree of tumor angiogenesis, but also on the growth pattern (solid versus``scirrhous'' type). 16 The purpose of our present study was to assess the relationship between the amount of scirrhous component in invasive ductal carcinoma and the morphologic and kinetic patterns on MR imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Although patients with increased VEGF demonstrated higher CD31 microvascular densities, no significant association between MRI parameters and these other surrogate markers was demonstrated (Su, Cheung et al 2003). In a study of 38 patients with advanced hepatocellular carcinoma treated with sunitinib, the investigators found significant decreases in K trans and K ep to approximately half.…”
Section: Dynamic Contrast Enhanced Mrimentioning
confidence: 97%